THE SPREAD OF ISLAM AND ITS IMPACTS ON THE ARABIC CALLIGRAPHY (KHAṬ) - Hasbullah, Abdur Ro’uf (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2022)
Language is a system of arbitrary sound symbols produced by human speech tools and used by the community in communicating, cooperating and identifying. Oral language is the primary language, while written language is a secondary language. Written languages change more slowly than corresponding spoken languages. The Arabic language itself belongs to the group of Semitic alphabetical letter in which mainly the consonants are represented in writing, while the markings of vowels are optional. With the spread of Islam, the Arabic alphabet was adapted by several non-Arab nations for writing their own languages. Actually, the earliest-known alphabet to humankind was the North Semitic, which developed around 1700 B.C. in Palestine and Syria. The Arabic, Hebrew, and Phoenician alphabets were based on this model. The North Arabic letter, which eventually prevailed and became the Arabic letter of the Quran, relates most substantially and directly to the Nabataean, which was derived from the Aramaic. Arabic letters until today still share with Aramaic the names of some alphabet letters. Arabic has influenced many other languages around the globe throughout its history.